2022
DOI: 10.1002/sd.2466
|View full text |Cite
|
Sign up to set email alerts
|

Natural resources, renewable energy, and governance: A path towards sustainable development

Abstract: Based on data for 48 African countries for the period 2000–2020, we analyse the effects of natural resources on renewable energy development and the mediating effects of governance on that relationship. For this purpose, the Ordinary Least Squares method was used to develop a baseline regression model, and the Generalized Method of Moments (GMM) approach was used for the dynamic model regression. Quantile regression was used for robustness checking across the various distributions of renewable energy. First, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 118 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…Australia, Japan, and Canada, among others have concentrated their efforts in rehabilitating existing large/small hydropower projects and building new small hydropower plants (Fujii et al, 2019; Gunturu & Hallgren, 2017; Wang et al, 2020). Nchofoung and Ojong (2022) showed that sustainable development of African nations is a direct outcome of the cumulative impacts of natural resources, renewable energy (mainly hydropower) and good governance. Moreover, IHA has specifically highlighted the advantages that hydropower development has over other renewables to attain net zero conditions in the future (IHA, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Australia, Japan, and Canada, among others have concentrated their efforts in rehabilitating existing large/small hydropower projects and building new small hydropower plants (Fujii et al, 2019; Gunturu & Hallgren, 2017; Wang et al, 2020). Nchofoung and Ojong (2022) showed that sustainable development of African nations is a direct outcome of the cumulative impacts of natural resources, renewable energy (mainly hydropower) and good governance. Moreover, IHA has specifically highlighted the advantages that hydropower development has over other renewables to attain net zero conditions in the future (IHA, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that resource‐rich countries experience deterioration in environmental sustainability compared to non‐resource countries in SSA. Related studies by Nchofoung & Ojong, (2023) focused on the pathway toward sustainable development by examining the role of governance in mediating the effects of natural resources on renewable energy. They found that African countries with efficient management of resources improved the development of renewable energy, depending on the type of natural resource used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This, in turn, will help reduce child mortality and enhance the development of human capital. Another important aspect is the financing of renewable energy, which must be given greater attention to promote sustainable development in Africa (Byaro et al, 2023; Kirikkaleli & Adebayo, 2021; Nchofoung & Ojong, 2023). Employing the revenue from natural resources into the provision of renewable energy will contribute to the achievement of Sustainable Development Goal 7 (Nchofoung & Ojong, 2023), which focuses on ensuring access to affordable, reliable, sustainable, and modern energy for all.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations